2021
DOI: 10.1371/journal.pone.0249043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus disease and Tele-Heart Failure Clinic on cardiovascular mortality and heart failure hospitalization in ambulatory patients with heart failure

Abstract: Background We sought to investigate the impact of the COVID-19 pandemic and the Tele-HF Clinic (Tele-HFC) program on cardiovascular death, heart failure (HF) rehospitalization, and heart transplantation rates in a cohort of ambulatory HF patients during and after the peak of the pandemic. Methods Using the HF clinic database, we compared data of patients with HF before, during, and after the peak of the pandemic (January 1 to March 17 [pre-COVID], March 17 to May 31 [peak-COVID], and June 1 to October 1 [pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Elective medical services declined markedly during the outbreak of COVID-19 in Taiwan [ 12 ]. The same phenomenon was observed similarly all over the world [ 2 , 3 , 4 , 6 , 7 ]. People were less willing to visit a hospital for fear of COVID-19, which was known to be contagious disease at the outset of the outbreak [ 13 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Elective medical services declined markedly during the outbreak of COVID-19 in Taiwan [ 12 ]. The same phenomenon was observed similarly all over the world [ 2 , 3 , 4 , 6 , 7 ]. People were less willing to visit a hospital for fear of COVID-19, which was known to be contagious disease at the outset of the outbreak [ 13 ].…”
Section: Discussionsupporting
confidence: 74%
“…The COVID-19 pandemic has resulted in an extensive transformation of health care systems worldwide [ 2 ]. A previous report from a single institute in Thailand found that readmission rates for heart failure patients were significantly lower during the peak of the COVID-19 pandemic and were slightly increased during the post-peak period of the COVID-19 pandemic in those managed with telemedicine [ 3 ]. Another single institute study from the United Kingdom revealed that postoperative infection after emergency general surgery during the COVID-19 pandemic was similar to that of the pre-COVID-19 period [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 104 Though virtual visits have been associated with better adherence to clinic follow-up (likely related to the relative ease of access and reduced burden of transportation), 105 video examination alone (without supplemental remote monitoring and laboratory data) may be particularly challenging in the evaluation of high-risk patients who need careful and safe adjustment of guideline-directed medical therapies. 106 , 107 Although assessing jugular venous distension and lower extremity edema by video examination is possible, supplemental data to inform intravascular volume status are frequently necessary for optimal decision-making. 67 , 108 The impact of televisits in place of in-person visits on outcomes is unknown and requires investigation.…”
Section: Management Of Heart Failure During the Covid-19 Pandemicmentioning
confidence: 99%
“…A decrease in emergency HF admissions was commonly reported by OPTIMIZE contributors, along with reduced outpatient activity, and fewer referrals to cardiac rehabilitation units. OPTIMIZE clinicians at a University hospital's HF clinic in Thailand observed a 16% reduction in the number of outpatient visits and a 22% decline in the number of hospitalizations during the peak of the pandemic, although there were no restrictions on hospitalizations for symptomatic patients; in addition, HF readmission rates were significantly lower than in the pre-COVID period (2.5% vs. 8.7%) [ 16 ]. In countries with high COVID-19 rates and already limited HF services, the reallocation of staff and facilities to care of patients with COVID-19 was particularly problematic.…”
Section: Challenges Of the Covid-19 Pandemic For The Continuity Of Hf...mentioning
confidence: 99%
“…The widely reported ‘techceleration’ triggered by the pandemic – with rapid adoption of more digital solutions for healthcare needs – had some benefits for patients with HF. In Thailand, OPTIMIZE coordinators reported that a telemedicine program was found to be effective in achieving target doses of guideline-directed medical therapy [ 16 ]. In Poland, clinicians in the OPTIMIZE network reported that, for those with a cardiac implantable electronic device such as an ICD or CRT, follow-up was largely shifted to remote device checks, with no harmful effect on device safety [ 21 ].…”
Section: Organizational Changes Reported To Help Ensure Continuity Of...mentioning
confidence: 99%